Formulation, Optimization, and In vivo Evaluation of Clozapine Loaded Transdermal Drug Delivery System for the Treatment of Schizophrenia (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: The present research work was intended to develop and optimize transdermal matrix patch ofclozapine using Box–Behnken experimental design (Box–Behnken design [BBD]) for improved bioavailability ascompared to oral formulation. The 3-factor, 3-level BBD was employed to investigate the combined influence offormulation variables on flux, tensile strength (TS), and in vitro drug release. The generated polynomial equationwas validated and desirability function was utilized for optimization. Materials and Methods: Optimizedformulation evaluated for physicochemical characterization, Fourier transform infrared, differential scanningcalorimetry, in vitro drug release, permeability enhancement potential by ex vivo, skin irritation, and in vivopharmacokinetics and stability studies. Results: The results of the optimized formulation (F15) showed TS of 6.84± 0.64 MPa, flux of 104.80 ± 1.39 (μg/h/cm2), and % drug release after 20 h (Q20) of 82.19 ± 1.12% which wasstable up to 6 months in accelerated condition. Observed and the predicted values of the responses were foundto be in good agreement. Optimized transdermal patch of clozapine found free from skin irritation as per Draizescore method. The pharmacokinetic result had shown the bioavailability of clozapine improved about 2.18-foldafter transdermal drug delivery when compared with oral marketed formulation. Discussion and Conclusion: Theresults of the study revealed that the developed transdermal patch of clozapine can be a promising alternativewhich provides effective management of schizophrenia in terms of improved patient compliance.